The Effectiveness of Internal Supervision of Regional Budget Performance and its Influence on Regional Economic Growth in South Buru District - Rahmat Dasuki; Teddy Ch. Leasiwal; Yerimias Manuhutu (LP2M IAIN Palopo, 2026)
Internal supervision of regional financial management is one of the factors that plays an important role in improving regional financial performance, especially in the aspect of Regional Expenditure. On the other hand, the dynamics of regional spanning realization are the main determinant of regional economic growth, especially for the regions with weak fiscal capacity support. Therefore, efforts to improve regional spending performance by increasing the effectiveness of internal regional financial supervision are obsolutely necessary. The purpose of this study is to analyze the effectiveness of internal financial supervision on budget performance and its influence on regional economic growth in South Buru Regency, for the LKPD years 2011 to 2024. For this purpose, the study uses multiple regression analysis supported by annual secondary time series data obtained from publications of the South Buru Regency Central Statistics Agency, and from the Maluku Representative Office of the Republik of Indonesia Audit Board. The results of this study indicate that variations in the number of supervisory findings (TPI) have a significant negative effect on regional budget performance (KAD), while variations on Follow-up actions according to recommendations (TLSR) have a positive effect but not statistically significant. Based on the results of the simultaneous F Test, the influence of variations in these two factors, TPI and TLSR on regional budget performance is not statistically significant, which is confirmed by the estimated value of the determination coefficient R2 of 0.338 which indicates that the effectiveness of internal supervision has not had an effective influence on regional budget performance. In another section, the results of this study show that variations in direct/capital spending (BLM) during the observation period had a significant positive effect on variations in regional economic growth. In addition, according to the results of the F Test, these two variables have a significant influence on regional economic growth with a coefficient of determination R2 of 0.751.